Akuntabilitas Memediasi Sistem Pengendalian Internal Pemerintah Dan Partisipasi Masyarakat Terhadap Transparansi Alokasi Dana Desa Di Kecamatan Mojoagung - Shendi Damora; Endah Susilowati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of the internal control system and community participation on the transparency of village fund allocations with accountability as a mediating variable, a case study on the Mojoagung District Government Village Apparatus. This research is a quantitative research. The data used is primary data through distributing questionnaires. The sample was determined by purposive sampling method of 90 respondents. The analysis technique uses SmartPLS 4.0. The results of the research show that a) the government's internal control system influences transparency and is proven to be true; b) The government's internal control system affecting accountability is not proven true; c) Public Participation affecting Transparency has not been proven true; d) Community Participation influencing Accountability has been proven true; e) Accountability affects Transparency is not proven true. In conclusion, the Government's Internal Control System contributes to Transparency, Community Participation Contributes to Accountability and Accountability does not mediate the Internal Control System and Community Participation for Transparency in Village Fund Allocations. Keywords: Accountability, Government Internal Control System, Community Participation, Transparency, Village Fund Allocation.